erilaku Belajar Siswa Di Sekolah Menengah Pertama Negeri 8 Manado - Wauran, Lineke Hesmi; Kaunang, Markus .; Londa, Very Y (JURNAL ILMIAH SOCIETY, 2015)
This research study analyzes the behavior of students in SMPN 8 Manado. The data used in this research is secondary data is data collected from interviews with informants and secondary data is data that is collected through the article, literratur, journals and internet sites). Based on the results of the study, researchers analyzed that study the behavior of the students at SMPN 8 Manado unfavorable. Like truant, did not want to do chores, like storytelling in the classroom, nonchalance cuh to lessons, often ask permission out while studying, and do not obey the rules. The behavior of students in learning, whether it's bad behavior and bad behavior can not be separated from the role and responsibilities of a teacher as an educator. Attitudes and behavior of a student in teaching and learning activities closely related to the role of the teacher in teaching. Bad behavior on the show by some students during the learning process, must be addressed by teachers in the classroom at the time.Â Keywords: Behavior, Learning, Student